Adequate Translation of the Poetic Text. Is it Equivalence or Correspondence? - Veličkienė, Deimantė (Vertimo studijos, 2021)
The article addresses the issue of adequate translation of poetry which is understood as the acceptable relationship between the original text and its translation. It provides an overview of the terms that are used in various theories to describe this acceptable relationship in poetry translation, and also of how this relationship is understood in sociosemiotic and hermeneutic translation studies. The article provides a more in-depth analysis of the concepts of equivalence and correspondence which are commonly used to define adequate translation. The author draws a conclusion that the concept of correspondence as a multiple analogue defines the acceptable relationship between the original text and its translation more adequately than the concept of equivalence. Finally, problematic aspects of poetry translation are discussed that the definition of correspondence fails to encompass.
Keywords: poetry translation; adequate translation; equivalence; correspondence; translation theory